Effect of fractional condensers on characteristics, compounds distribution and phenols selection of bio-oil from pine sawdust fast pyrolysis. Issue 2 (April 2020) - Chai, Meiyun; He, Yifeng; Nishu; Sun, Chen; Liu, Ronghou
Abstract: Bio-oil is a multicomponent mixture of more than 400 types of organic compounds, with high water content. Fractionation of bio-oil may be a more efficient approach for primary separation of bio-oil. In this work, to better understand the effect of fractional condensers on bio-oil yield, physicochemical characteristics, compounds distribution and phenols selection during biomass fast pyrolysis process, a semi-automatic controlled fluidized bed reactor biomass fast pyrolysis system with four-stage condensers was developed. Average temperatures of Condensers 1, 2, 3, 4 were 32.39 °C, 26.74 °C, 24.06 °C and 23.68 °C, respectively. And the bio-oil yields of Condenser 1, 2, 3, and 4 were 26.82%, 7.31%, 1.48% and 9.69%, respectively. Bio-oil collected from Condenser 4 had the lowest water content (9.68 wt%), the lowest acidity (pH = 3.67), and the highest HHV (29.2 MJ/kg). The highest relative contents of compounds collected from Condenser 1, 2, 3 and 4 were 1-(4-hydroxy-3-methoxyphenyl)-2-Propanone (6.95%), trans-Isoeugenol (6.63%), Creosol (5.28%), and trans-Isoeugenol (6.69%), respectively. Fractional condensers affected the compounds distribution, but it has a stronger effect on relative heavy compounds (molar mass > 250) and a weaker effect on relative light compounds (molar mass < 200). Fractional condensers were more conducive to the selection of phenols with relative yield of more than 30%. Phenols, acids and furfurans tended to distribute at higher temperature, while alcohols, ethers and hydrocarbons tended to distribute at relative lower temperature, but the difference was small. The research has provided a reference for the production of bio-oil. Graphical abstract: Image 1 Highlights: The higher heating value of bio-oil collected from the fourth condenser is around 3/4 of crude oil. The lower the condensing temperature is, the less water content, and the higher HHV of bio-oil are. Fractional condensers have stronger effect on heavy compounds and weaker effect on light compounds. Fractional condensers were more conducive to the selection of phenols with relative yield of more than 30%.